2012
DOI: 10.1371/journal.pone.0044237
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Hepatic Antioxidant Gene Expression in Mice

Abstract: BackgroundThis study was aimed to examine circadian variations of hepatic antioxidant components, including the Nrf2- pathway, the glutathione (GSH) system, antioxidant enzymes and metallothionein in mouse liver.Methods and ResultsAdult mice were housed in light- and temperature-controlled facilities for 2 weeks, and livers were collected every 4 h during the 24 h period. Total RNA was isolated, purified, and subjected to real-time RT-PCR analysis. Hepatic mRNA levels of Nrf2, Keap1, Nqo1 and Gclc were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 39 publications
11
102
0
2
Order By: Relevance
“…2a), results consistent with findings in peritoneal macrophages ( Supplementary Fig. 1a) and with the diurnal variation observed by Xu and colleagues in liver tissue 12 .…”
Section: Heme Degradation Is Regulated By the Circadian Clocksupporting
confidence: 92%
“…2a), results consistent with findings in peritoneal macrophages ( Supplementary Fig. 1a) and with the diurnal variation observed by Xu and colleagues in liver tissue 12 .…”
Section: Heme Degradation Is Regulated By the Circadian Clocksupporting
confidence: 92%
“…34 Circadian regulation of Nrf2 is controlled by BMAL/CLOCK transcription factors and mediates rhythmic control of GSH levels as well as diurnal variation in drug-induced toxicity. 35,36 It has been reported that age-dependent alterations in the reduced versus oxidized ratio of glutathione (GSH/GSSG) significantly affects the redox state of the tissues. 37 These studies, although not definitive, suggest that decreases in total GSH and/or reduced/oxidized ratio of GSH may be mediated, in large part, by the impaired activation of Nrf2 in aging.…”
Section: Nrf2 In Cellular Redox Homeostasismentioning
confidence: 99%
“…Melatonin is involved in biological clock function and its secretion reaches peak value after midnight. It has direct antioxidant activity: up regulates antioxidant enzymes, enhances non-enzymatic antioxidants and modulates NO bioavailability (Chakravarty and Rizvi, 2011;Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, diurnal fluctuations of antioxidant enzymes activity was documented in mammals including humans (Singh et al, 2005;Xu et al, 2012). The PON1 is one of antioxidant enzymes protecting against oxidative damage (Nezami et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation